Biophysical Determinants for Cellular Uptake of Hydrocarbon-Stapled Peptide Helices - Bird, Gregory H. (Nat Chem Biol, 2016)
Hydrocarbon-stapled peptides are a class of bioactive alpha-helical ligands developed to dissect and target protein interactions. While there is consensus that stapled peptides can be effective chemical tools for investigating protein regulation, their broader utility for therapeutic modulation of intracellular interactions remains an active area of study. In particular, the design principles for generating cell-permeable stapled peptides are empiric, yet consistent intracellular access is essential to in vivo application. Here, we used an unbiased statistical approach to determine which biophysical parameters dictate the uptake of stapled peptide libraries. We found that staple placement at the amphipathic boundary combined with optimal hydrophobic and helical content are the key drivers of cellular uptake, whereas excess hydrophobicity and positive charge at isolated amino acid positions can trigger membrane lysis at elevated peptide dosing. Our results provide a design roadmap for maximizing the potential to generate cell-permeable stapled peptides with on-mechanism cellular activity.